2006
DOI: 10.1063/1.2402346
|View full text |Cite
|
Sign up to set email alerts
|

The impact of negative-bias-temperature-instability on the carrier generation lifetime of metal-oxynitride-silicon capacitors

Abstract: Articles you may be interested inAn accurate characterization of interface-state by deep-level transient spectroscopy for Ge metal-insulatorsemiconductor capacitors with SiO2/GeO2 bilayer passivation J. Appl. Phys. 112, 083707 (2012); 10.1063/1.4759139Identification of the atomic-scale defects involved in the negative bias temperature instability in plasma-nitrided p -channel metal-oxide-silicon field-effect transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
1
21
1
Order By: Relevance
“…6 around E V + 0.3–0.4 eV could correspond with the donor states of the P b centre 15. The DLTS peak corresponding with P b centres in Si is well‐established in the literature 33–38 with activation energy around E V + 0.3 eV in p‐type Si. Another factor which needs to be accounted for is the occurrence of hydrogen passivation, which is very effective in reducing the active P b concentration 30, 39, 40 and which may be different between the samples studied in DLTS and ESR.…”
Section: Discussionmentioning
confidence: 67%
“…6 around E V + 0.3–0.4 eV could correspond with the donor states of the P b centre 15. The DLTS peak corresponding with P b centres in Si is well‐established in the literature 33–38 with activation energy around E V + 0.3 eV in p‐type Si. Another factor which needs to be accounted for is the occurrence of hydrogen passivation, which is very effective in reducing the active P b concentration 30, 39, 40 and which may be different between the samples studied in DLTS and ESR.…”
Section: Discussionmentioning
confidence: 67%
“…Of course, we cannot completely neglect the possibility that the near mid-gap peaks are related to so-called "generation transients" in a MOS capacitor, which occur after the application of a pulse from deep depletion into accumulation [13,14]. Minority carrier generation by deep levels at the interface or in the depletion region plus carrier diffusion from the neutral substrate will give rise to a capacitance increase by the build-up of an inversion layer after the pulse.…”
Section: Resultsmentioning
confidence: 97%
“…The increase found at and above room temperature may originate from minority carrier generation in the depletion region. 2,14,34,35 The latter response differs from a true electron emission spectrum and is typical for a MOS capacitor, biased in deep depletion. It originates from the minority carrier generation either by thermal Shockley-Read-Hall (SRH) carrier generation by deep levels in the depletion region or by the diffusion of minority carriers (holes) from the neutral region toward the negatively biased gate.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that both in the zero-dot reference sample and in the Ge QD capacitors, two prominent features are present: a peak in the 150-200 K range which is most likely related to so-called dangling bond P b centers and a peak at or above room temperature, which could be related to the so-called minority carrier generation in a MOS capacitor. 34,35 The main impact of the presence of the Ge QDs is the change in the V FB toward more positive values with increasing QD size and indicating the introduction of negative charge and, secondly, the increase in the counterclockwise hysteresis in the C-V curves between a forward and a reverse bias sweep, which is a fingerprint of more pronounced charge trapping. * Electrochemical Society Fellow.…”
mentioning
confidence: 99%